Quantitative Thermal Imaging : Condition monitoring and healthcare diagnostics. Issue 1 (11th January 2023) - Simpson, Rob; McMillan, Jamie; Hayes, Michael; Bond, Wesley; Panicker, Vivek; Korniliou, Sofia; Machin, Graham
Quantitative thermal imaging, the measurement of temperature by use of thermal imaging devices, is reviewed here from a metrological perspective with a focus on measurement confidence and system application to fields such as condition monitoring and healthcare diagnostics. Thermal imaging has seen greatly increased application for the measurement of temperature following dramatic improvements in practicality and price. Selected thermal imaging systems are reviewed here by providing some example measurements outputs from devices, highlighting their outcomes on measurement confidence and impact on practical use, such as in condition monitoring and healthcare diagnostics.